2018
DOI: 10.1590/18069657rbcs20160393
|View full text |Cite
|
Sign up to set email alerts
|

Is Structural Quality as Assessed by the "Profil Cultural" Method Related to Quantitative Indicators of Soil Physical Quality?

Abstract: Soil and crop management systems change the soil structure, thereby affecting soil quality. The "profil cultural" method (PCM) has been used to identify the effects of management systems on soil structure; however, few studies relate the structures identified by the PCM to quantitative indicators of soil structural quality. This study aimed to quantify soil structures using the PCM and relate these structures to bulk density (Bd), critical bulk density (Bdc), soil aeration capacity (ε a ), least limiting water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
3
3
0
Order By: Relevance
“…These results are in accord with Possamai et al (2022), Silva et al (1997) For comparison of bulk density in (CT) and (MT) management, Figures 4 and 5 showed a value lower than 1.39 Mg m -3 for CT, the "overall effect" is -0.02 ± 0.01, indicating an interval of values between 1,36-1,38 Mg m -3 and MT the "overall effect" is equal to -0.07 ± 0.01, indicating an interval of values between 1,31-1,33 Mg m -3 . These results are in accord with, Reichert et al (2009), Portella et al (2012), Giarola et al (2013), Guimarães et al (2013), Tavares et al (2014), Moncada et al (2014), Carducci et al (2017), Boizard et al (2017), Macedo et al (2017), Watanabe et al (2018), Inagaki et al (2021). 1,36-1,38 Mg m and MT the "overall effect" is equal to -0.07 ± 0.01, indicating an interval of values between 1,31-1,33 Mg m -3 .…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…These results are in accord with Possamai et al (2022), Silva et al (1997) For comparison of bulk density in (CT) and (MT) management, Figures 4 and 5 showed a value lower than 1.39 Mg m -3 for CT, the "overall effect" is -0.02 ± 0.01, indicating an interval of values between 1,36-1,38 Mg m -3 and MT the "overall effect" is equal to -0.07 ± 0.01, indicating an interval of values between 1,31-1,33 Mg m -3 . These results are in accord with, Reichert et al (2009), Portella et al (2012), Giarola et al (2013), Guimarães et al (2013), Tavares et al (2014), Moncada et al (2014), Carducci et al (2017), Boizard et al (2017), Macedo et al (2017), Watanabe et al (2018), Inagaki et al (2021). 1,36-1,38 Mg m and MT the "overall effect" is equal to -0.07 ± 0.01, indicating an interval of values between 1,31-1,33 Mg m -3 .…”
Section: Resultssupporting
confidence: 84%
“…1,36-1,38 Mg m and MT the "overall effect" is equal to -0.07 ± 0.01, indicating an interval of values between 1,31-1,33 Mg m -3 . These results are in accord with, Reichert et al (2009), Portella et al (2012), Giarola et al (2013), Guimarães et al (2013), Tavares et al (2014), Moncada et al (2014), Carducci et al (2017), Boizard et al (2017), Macedo et al (2017), Watanabe et al (2018), Inagaki et al (2021). These results indicate that soil density is a dynamic property that varies with the structural conditions of the crop soil (Bauder et al, 1981;Jones, 1983), according to soil texture and the type of management adopted.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Likewise, Guimarães et al (2014) observed higher PR in open-grown coffee than in shaded coffee areas. Our findings agree with Watanabe et al (2018) andTavares Filho et al (2012) in the same soil type and under a no-till system, in Londrina, Paraná State (Brazil).…”
Section: Soil Penetration Resistance (Pr)supporting
confidence: 88%